Tarım alanında kullanılan traktörlerin i̇nsan vücuduna yaptığı titreşimin etkisi - Karabulut, Abdurrahman (Afyon Kocatepe Üniversitesi)
Bu araştırmanın amacı, traktörlerde titreşim sorunlarını inceleyebilmek; traktör oturak ve sürücünün temel titreşim ve yalıtım özelliklerini tespit etmek, gelecekte yapılacak traktör oturak tasarımına faydalı veriler araştırmaktır.

The objective of the research is to determine the basic vibration and vibration isolation characteristics of tractor, seat and driver in order to enlighten the vibration problems associated with tractors and is to produce data which will be useful for tractor seat design.
Effect of vibration of tractors used in agricultural fields on human body
Keywords: Titreşim; Titreşim Yalıtımı; Traktör Oturakları; Yalıtım Sistemleri; Vibration; Vibration Isolation; Tractor Seat; Isolation Systems